2021
DOI: 10.1002/adma.202006644
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom‐Up Approach to Red‐Emitting Molecular‐Based Nanoparticles with Natural Stealth Properties and their Use for Single‐Particle Tracking Deep in Brain Tissue

Abstract: Fluorescent nanoparticles dedicated to bioimaging applications should possess specific properties that have to be maintained in the aqueous, reactive, and crowded biological environment. These include chemical and photostability, small size (on the scale of subcellular structures), biocompatibility, high brightness, and good solubility. The latter is a major challenge for inorganic nanoparticles, which require surface coating to be made water soluble. Molecular‐based fluorescent organic nanoparticles (FONs) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…This result is in accordance with their stealthy behavior previously observed toward HeLa cells. 20 Most interestingly, we observed the same lack of interactions for Q BDtF FONs. Q BDvF FONs, on the other hand, could readily be observed accumulated inside of cells.…”
Section: ■ Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…This result is in accordance with their stealthy behavior previously observed toward HeLa cells. 20 Most interestingly, we observed the same lack of interactions for Q BDtF FONs. Q BDvF FONs, on the other hand, could readily be observed accumulated inside of cells.…”
Section: ■ Methodssupporting
confidence: 74%
“…We had previously reported that the remarkable absorption and significant fluorescence quantum yield of Q BDF let its FONs reach a giant 1P brightness of 1 × 10 7 M −1 cm −1 . 20 We now report that these FONs also display a huge 2P brightness of 6 × 10 5 GM. Interestingly, the excellent properties of Q BDtF FONs described above make them our second brightest probe, with the foremost advantage that both its absorption and emission are red-shifted as compared to Q BDF .…”
Section: ■ Methodsmentioning
confidence: 49%
See 2 more Smart Citations
“…However, controlling the fate of FONs in cellular environments has been seldom addressed. We have recently reported on two dye designs, bis-dipolar [ 28 ] and quadrupolar [ 29 ], that yield spontaneously stealth FONs. We then modulated the π-conjugation of the quadrupolar template of the composing chromophores to yield FONs of red-shifted emission.…”
Section: Introductionmentioning
confidence: 99%